Contribution of Fiber Undulation to Mechanics of Three‐Dimensional Collagen‐I Gel. Issue 1 (July 2016) - Lin, Shengmao; Gu, Linxia
Summary: The collagen‐I gel is extensively used as a scaffold material in tissue engineering due to its ability to mimic the extracellular matrix (ECM). In this study, the mechanics of collagen‐I gel is investigated using a numerical model of three‐dimensional collagen network. The resulted mechanical behavior was validated against the published experimental data. Results illustrated that fiber alignment was dominated in the low strain region, and its transition to stretching dominated phenomena at higher strain led to the strain stiffening of collagen gel. The collagen undulation at the microscopic level was found to delay the initiation of strain stiffening.